Qualitative Study of Solid Medical Waste Management at dr. R. Koesma Regional Hospital, Tuban, East Java - Luly Ervidiana; Yuli Peristiowati; Agusta Dian Ellina (Journal of Health Promotion and Behavior, 2024)
Background: Activities in the hospital generate various kinds of waste. One of them is medical waste. Medical waste is part of the Hazardous and Toxic Material (HTM) waste which is very dangerous if it is disposed of directly at the Final Disposal Site (FDS). This study aimed to determine the management of Solid Medical Waste at RSUD dr. R.  Koesma, Tuban Regency. Subjects and Method: A qualitative research with interviews was conducted at RSUD Dr. R.  Koesma, Tuban Regency, East Java in March 2022. Participants consisted of 27 informants and 2 source triangulations. Data transcripts were analyzed using content analysis. Results: Human Resources involved in solid medical waste management are all employees or employees who work at dr. R.  Koesma Regional Hospital, Tuban, East Java which produces waste. All waste management hospital staff have received medical waste training through PPI training, solid medical waste management has been labeled. The transportation of solid medical waste does not have a special route for transportation to garbage dump but instead uses the same route used by visitors to the hospital. Conclusion: Waste management hospital staff have received medical waste training through PPI training, solid medical waste management at dr. R.  Koesma Hospital Tuban has been going well.